EFEKTIVITAS PENGELOLAAN MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS DAN MENJAGA TINGKAT LIKUIDITAS (Studi Penelitian Pada KUD “Karya Bhakti” Jombang Tahun 2011-2015) - Nola Rektasiwi Okila; Fransisca Yaningwati; Dwiatmanto Dwiatmanto (Fakultas Ilmu Administrasi Universitas Brawijaya, 2016)
The use of net working capital, or working capital is very important for the analyzer internally and externally, in addition to the problem of working capital is closely related to the company's daily operations also indicates the level of security or margin of savety creditors mainly short-term creditors. The purpose of this study was to determine the effective management of working capital at KUD “Karya Bhakti” towards increased profitability and maintain liquidity. Type of research include descriptive using a case study approach. The research location KUD